Debt Redemption Fund: Conditio Sine Qua Non? Government Bonds in the Euro Area Crisis - Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Fiscal austerity has not led to a return of confidence and it is not at all certain that the current crisis strategy can be sustained politically and will eventually succeed. Government bonds of crisis-hit countries have lost their safe asset status and high risk premiums are impairing monetary transmission. Within its mandate the ECB is in principal able to do what it takes to put an end to this crisis, but only if euro area governments tow the same line. A well-designed debt redemption fund could restore confidence and enhance growth by repairing the monetary transmission mechanism and allowing the expansionary monetary policy of the ECB to reach the crisis-hit countries. Combined with additional policies to foster growth and rebalancing in the euro area, a temporary debt redemption fund could be instrumental in engineering an economic turn-around. The paper touches upon the recent OMT-decision of the German Federal Constitutional Court, euro(basket)bonds and eurobills.
urn:nbn:de:101:1-2014031112505
Keywords: 330; Debt Redemption Fund; OMT; safe assets; TARGET2; constitutional court; current account imbalances